Analisis Kesesuaian Antara Harapan dan Kinerja Layanan pada Kualitas Pelayanan Hotel Akbar Syariah Banyumas Jawa Tengah - Fisit Suharti (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
At globalization era, product or service that compete in market are so many and medley, it consequence for openness of market. So it happens, competition between producer to can full the consumer requirement and give satisfactions for customer maximally. Because, basically the purpose of business is to make satisfied for customer. Customer satisfied is feeling degree of customer after comparing between what is accepted and expectation. One of step for satisfactory the customer is with give service for customer well. With good service in a business, it will make satisfied for customer. After the customers feel satisfaction with product or service that accepted, the customer will compare the service. Akbar Hotel Syariah Banyumas is the first Syariah Hotel in Banyumas. According to research that have done, it get conclusion that not suitable between expectation and satisfactions of consume yet to service quality observation from Tangible, Reliability, Responsiveness, and Empathy dimension. But for assurance dimension to indicate have any suitable.